The Impact of Minimal Response Strategy on the Students’ Speaking Skill to the Tenth Grade Students of State Senior High School 10 Palembang - Yuspar Uzer (ELTE Journal (English Languange Teaching and Education), 2018)
AbstractThe problem of this study is formulated into the following question: ‘Is there any significant impact of minimal response strategy on the student’s speaking skill of the tenth grade of state Senior High School 10 of Palembang?. It can be concluded that the impact of Minimal Response Strategy to the students’ speaking skill of state Senior High School 10 of Palembang was significant. It can be seen from the result of pre-test and post-test scores.The students average score in pre-test was 14, 10. The highest score was 18 which were achieved by two students, while the lowest score was 9 which were achieved by two students. The students average score in post-test was 15, 32. The highest score was 18 which were achieved by three students, while the lowest score was 13 which were achieved by seven students. From the result of the matched t-test, it was found that the t-obtained was higher than t-table value. The result of matched t-test formula was 2.77 and t-critical value of t-distribution table was 2.68. It means that the alternative hyphotesis (Ha) with 0, 05% significance level in one tailed testing was accepted consequently and the null hyphothesis (Ho) was rejected. It is concluded that minimal response strategy is effective to improve students’ speaking ability. Keywords: impact of minimal response strategy, speaking skill, improve students’ speaking ability